Seasonality and relative abundance of Tabanidae (Diptera) captured on horses in the Pantanal, Brazil - Antonio Thadeu M Barros (Memorias do Instituto Oswaldo Cruz, 2001)
Once a month, from June 1992 to May 1993, collections of tabanids on horse were conducted in the Nhecolândia, Pantanal State of Mato Grosso do Sul, Brazil. Tabanid catches using hand nets were conducted from sunrise to sunset at grassland and cerradão (dense savanna) habitats. A total of 3,442 tabanids from 21 species,12 genera, and 3 subfamilies were collected. Although species abundance varied seasonally depending on habitat, no habitat specificity was observed for the most abundant species. In the grassland, 1,625 (47.2%) tabanids belonging to 19 species were collected, while 1,817 (52.8%) tabanids from 17 species were caught in the cerradão. The number of tabanid species varied from 7 during winter (July/August) to 15 in the spring (October). Tabanus importunus (56%) was the most abundant species, followed by T. occidentalis (8.2%), and T. claripennis (8.1%). The tabanid peak, in October, coincided with the beginning of the rainy season. The population peak of most species, including those with higher vector potential, suggests that the rainy season can be considered as the period of potentially higher risk of mechanical transmission of pathogens by tabanids to horses in the region.